Prevalence of high-risk human papillomavirus infection among women with diabetes mellitus in Accra, Ghana - Yacoba Atiase; Kofi Effah; Comfort Mawusi Wormenor; Ethel Tekpor; Esu Aku Catherine Morkli; Eunice Boafo; Ernest Yorke; Robert Aryee; Nana Owusu Mensah Essel; Stephen Danyo; Seyram Kemawor; Josephine Akpalu (BMC, 2024)
Abstract Background There is increasing evidence of a higher risk and poorer prognosis of cervical cancer among women with diabetes mellitus (DM) compared to the general population. These are mediated by higher susceptibility to persistent high-risk human papillomavirus (hr-HPV) infection due to dysfunctional clearance in an immunocompromised state. We aimed to determine the prevalence of hr-HPV infection and cervical lesions in a cohort of women with DM in Ghana. We further disaggregated the prevalence according to DM type and explored factors associated with hr-HPV infection. Methods This retrospective descriptive cross-sectional study assessed 198 women with DM who underwent cervical screening via concurrent hr-HPV DNA testing and visual inspection with acetic acid in an outpatient department of the National Diabetes Management and Research Centre in Korle-Bu Teaching Hospital, Accra from March to May 2022. Univariate and multivariable binary logistic regression were used to explore factors associated with hr-HPV positivity. Results Among 198 women with DM (mean age, 60.2 ± 12.1 years), the overall hr-HPV prevalence rate was 21.7% (95% CI, 16.1-28.1), disaggregated as 1.5% (95% CI, 0.3-4.4) each for HPV16 and HPV18 and 20.7% (95% CI, 15.3-27.0) for other HPV genotype(s). Respective hr-HPV prevalence rates were 37.5% (95% CI, 15.2-64.6) for type 1 DM, 19.8% (95% CI, 13.9-26.7) for type 2 DM, and 25.0% (95% CI, 8.7-49.1) for unspecified/other DM types. Past use of the combined contraceptive pill independently increased the risk of hr-HPV infection by approximately three times (adjusted odds ratio [aOR] = 2.98; 95% CI, 1.03 − 8.64; p-value = 0.045), whereas each unit increase in FBG level increased the odds of hr-HPV infection by about 15% (aOR = 1.15; 95% CI, 1.02 − 1.30; p-value = 0.021). Conclusion Our study points to a high prevalence of hr-HPV among women with DM and highlights a need for glycemic control among them as this could contribute to lowering their odds of hr-HPV infection. The low overall rates of HPV vaccination and prior screening also indicate a need to build capacity and expand the scope of education and services offered to women with DM as regards cervical precancer screening.